2022
DOI: 10.1265/ehpm.22-00027
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution exposure and mammographic breast density in Tehran, Iran: a cross-sectional study

Abstract: Background: Air pollution is one of the major public health challenges in many parts of the world possibly has an association with breast cancer. However, the mechanism is still unclear. This study aimed to find an association between exposure to six criteria ambient air pollutants (PM 2.5 , PM 10 , SO 2 , NO 2 , O 3 , and CO) and mammographic breast density (MBD), as one of the strongest predictors for developing breast cancer, in women living in Tehran, Iran. Methods: Participants were selected from women at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The findings of the Global Burden of Disease in 2019 showed that air pollution, as a major level 2 risk factor for the global burden of disease, has become the fourth leading cause of globally attributable mortality (5). Previous studies have shown that air pollution affects people's health (6,7). The World Health Organization estimates that 7 million deaths occur globally each year due to air pollution, with 7% of these deaths attributed to pneumonia (8).…”
Section: Introdutionsmentioning
confidence: 99%
“…The findings of the Global Burden of Disease in 2019 showed that air pollution, as a major level 2 risk factor for the global burden of disease, has become the fourth leading cause of globally attributable mortality (5). Previous studies have shown that air pollution affects people's health (6,7). The World Health Organization estimates that 7 million deaths occur globally each year due to air pollution, with 7% of these deaths attributed to pneumonia (8).…”
Section: Introdutionsmentioning
confidence: 99%